VISIT-TO-VISIT AND 24-H BLOOD PRESSURE VARIABILITY: ASSOCIATION WITH ENDOTHELIAL AND SMOOTH MUSCLE FUNCTION IN AFRICAN AMERICANS - Diaz, Keith M. (2013)
The purpose of this study was to investigate the association of visit-to-visit and 24-h BP variability with markers of endothelial injury and vascular function. We recruited 72 African Americans who were non-diabetic, non-smoking, and free of cardiovascular and renal disease. Office BP was measured at three visits and 24-h ambulatory BP monitoring was conducted to measure visit-to-visit and 24-h BP variability, respectively. The 5-min time-course of brachial artery flow-mediated dilation and nitroglycerin-mediated dilation were assessed as measures of endothelial and smooth muscle function. Fasted blood samples were analyzed for circulating endothelial microparticles. Significantly lower CD31+CD42− endothelial microparticles were found in participants with high visit-to-visit SBP variability or high 24-h DBP variability. Participants with high visit-to-visit DBP variability had significantly lower flow-mediated dilation and higher nitroglycerin-mediated dilation at multiple time-points. When analyzed as continuous variables, 24-h mean arterial pressure variability was inversely associated with CD62+ endothelial microparticles; visit-to-visit DBP variability was inversely associated with flow-mediated dilation normalized by smooth muscle function and was positively associated with nitroglycerin-mediated dilation; and 24-h DBP variability was positively associated with nitroglycerin-mediated dilation. All associations were independent of age, gender, BMI, and mean BP. In conclusion, in this cohort of African Americans visit-to-visit and 24-h BP variability were associated with measures of endothelial injury, endothelial function, and smooth muscle function. These results suggest that BP variability may influence the pathogenesis of cardiovascular disease, in part, through influences on vascular health.